Impact of Day 7 Blastocyst Transfer on Obstetric and Perinatal Outcome of Singletons Born After Vitrified-Warmed Embryo Transfer - Huang, Jiaan; Yang, Xiaoyan; Wu, Jiayi; Kuang, Yanping; Wang, Yun (Frontiers in Physiology, 2020)
Background: Extended embryo culture have been reported to affect perinatal outcome regarding higher risks of large for gestational age (LGA)and preterm birth (PTB)yet decreased risk of small for gestational age (SGA). However, existing data about the obstetric outcome and the safety for offspring resulting from transfer of day 7 blastocyst is rare. Objectives:To compare obstetric and perinatal outcome using embryos vitrified on day 7 with those vitrified on day3, day5 and day6. Methods:Data were collected from 4489 infertile women who gave birth to live-born singletons after vitrified-warmed embryo transfer cycles from January 1st 2006 to December 31th 2017. Singletons were compared depending on the age of embryos. Main perinatal outcome parameters included PTB (gestational age <37 weeks), very PTB (VPTB, gestational age <32weeks), LGA (birthweights >90th percentiles), and SGA (birthweights <10th percentiles).Obstetric outcome included gestational diabetes (GDM), pregnancy-induced hypertension (PIH), premature rupture of membranes (PPROM), pre-eclampsia, placenta previa, placental abruption and postpartum hemorrhage.Propensity score matching (PSM) was used to adjust the confounding factors across groups and then analyze the association between in vitro culture period and the outcome measures. Results: After PSM, the transfer of day 7 blastocysts was associated with higher birth weight Z-scores and increased incidence of VLGA compared with the transfer of day 3 cleavage-stage embryoswhile the incidence of PTB, LBW, SGA did not reach statistical significance. Moreover, comparable perinatal outcome was found in comparison of day 7 vs. day 5 and day 7 vs. day 6. Furthermore, day 7 blastocysts did not result in adverse obstetric outcome compared with day 3, day 5 and day 6 embryos, respectively. Conclusions:In vitrified-warmed transfer cycles,day 7 blastocysts was associated with adverse perinatal outcome regarding higher risk of VLGA compared with day 3 cleavage-stage embryo, while blastocysts with diverse growth rates embrace similar developmental viability regardless of blastocysts vitrified on day 5, day 6 or day 7.